Comprehensive Characterization of Energy Saving and Environmental Benefits of Campus Photovoltaic Buildings - Jie Yang; Baorui Cai; Jingyu Cao; Yunjie Wang; Huihan Yang; Ping Zhu (Energies, 2023)
The development of campus photovoltaic buildings is a promising way to solve the problem of high energy consumption in colleges and universities. However, comprehensive study on their energy saving and environmental benefits is still insufficient. In this study, a theoretical model of a photovoltaic building roof system was preliminarily built, and the main factors affecting the power generation of campus photovoltaic buildings were analyzed. Furthermore, an experimental test platform for the campus photovoltaic building system was built, and a dynamic grid-connected strategy of “spontaneous self-use, surplus electricity connected to the grid” was creatively proposed, which points out that the grid connection rate in winter and summer vacations are about 15% and over 40%, respectively, and the annual grid connection rate is 25%. The result shows that the electricity input of the campus photovoltaic building can bear nearly 30% of the school’s annual electricity supply, which reduces the comprehensive energy consumption per unit area and per capita comprehensive energy consumption of the campus by more than 20%. The economic and environmental benefits of the 130,000 square meter campus photovoltaic building in the article are 38.8 million CNY and 20.12 million CNY, respectively, and the static investment payback period is about 7 years. The results show considerable reference value to the upgrading of campus photovoltaic buildings.